Angiogenic and Osteogenic Potential of Bone Repair Cells for Craniofacial Regeneration - Kaigler, Darnell (Mary Ann Liebert, Inc., 2010)
There has been increased interest in the therapeutic potential of bone marrow derived cells for tissue engineering applications. Bone repair cells (BRCs) represent a unique cell population generated via an ex vivo, closed-system, automated cell expansion process, to drive the propagation of highly osteogenic and angiogenic cells for bone engineering applications. The aims of this study were (1) to evaluate the in vitro osteogenic and angiogenic potential of BRCs, and (2) to evaluate the bone and vascular regenerative potential of BRCs in a craniofacial clinical application. BRCs were produced from bone marrow aspirates and their phenotypes and multipotent potential characterized. Flow cytometry demonstrated that BRCs were enriched for mesenchymal and vascular phenotypes. Alkaline phosphatase and von Kossa staining were performed to assess osteogenic differentiation, and reverse transcriptase–polymerase chain reaction was used to determine the expression levels of bone specific factors. Angiogenic differentiation was determined through in vitro formation of tube-like structures and fluorescent labeling of endothelial cells. Finally, 6 weeks after BRC transplantation into a human jawbone defect, a biopsy of the regenerated site revealed highly vascularized, mineralized bone tissue formation. Taken together, these data provide evidence for the multilineage and clinical potential of BRCs for craniofacial regeneration.